Risk and reliability. The alternative of categories and problems of their formalization - Корнійчук, М. Т.; Романов, О. І.; Совтус, І. К.; Шутко, М. О. (Proceedings of National Aviation University (archive), 2000)
Investigated are methodological aspects of conception and definition of risk and reliability. Definitions of this category were proposed. The probability model of risk estimation was built